Paramaterizing the shariah rulings for partnership financial transactions - Che Arshad, Noraziah; Ismail, Abdul Ghafar (Universiti Utara Malaysia Press, 2012)
Partnership-based was widely practised in the pre-Islamic period.The practice was so commonly prevalent among the muslim and non-muslim.This book is hoped to be of assistance to those who wish to discover the shariah contracts for partnership and the methods of structuring the current Islamic financial products and instruments through adopting either an existing Islamic contract or by combining two or more thereof.As for students and lecturers, this book is sought to be a reference for Islamic banking and finance related courses.It can also be a reference to the general members of the public who are interested to learn about the basic principles in the paramaterizing the shariah rulings for Islamic partnership contracts and to obtain issues about the Islamic banking and financial products.All readers may realize, that the first two chapters have briefly discussed the introduction to fiqh and shariah and the rule-making process of the areas in Islamic law.The main purpose of the book is to provide a more comprehensive understanding of the principles and basis of adopting the shariah contracts for Islamic financial products, as well as enabling the harmonization of the Islamic financial practices into shariah parameters of each contract.Nevertheless, the basic and important discussion on fiqh, shariah and the procedure of law-making process is believed tobe sufficiently covered in this book.